Cooled Radio Frequency Ablation for the Treatment of Osteoarthritis-Related Knee Pain: Evidence, Indications, and Outcomes - Oladeji, Lasun O.; Cook, James L. (The Journal of Knee Surgery, 2019)
Knee osteoarthritis (OA) is a common condition associated with pain and physical impairment in a large segment of the population. The traditional treatment algorithm progresses from conservative modalities to nonsurgical options to surgical intervention. Surgical intervention often provides reliable pain relief but not all patients are surgical candidates and there are some patients who prefer not to have surgery. Cooled radio frequency ablation (C-RFA) is a treatment with the potential to provide pain relief for patients who no longer benefit from noninvasive modalities and who desire an alternative to surgery. The objective of this review article is to provide the rationale, available evidence, indications, and outcomes associated with C-RFA for the treatment of chronic knee OA. A total of eight reports that use C-RFA in the treatment of chronic knee pain were identified and analyzed. There were two prospective trials, one retrospective cohort study, and five case reports or case series. C-RFA is an emerging procedure with encouraging early results; however, additional long-term prospective clinical trials are necessary to further characterize how C-RFA can best be used to treat chronic knee pain.
Keywords: osteoarthritis; cooled radio frequency ablation; chronic knee pain; alternative pain relief options